The Association between Vascular Endothelial Growth Factor (VEGF) Expression and Various Pathological Parameters of Squamous Cell Carcinoma of Uterine Cervix in Sanglah General Hospital - datui, annie minerva; Winarti, Ni Wayan; Maker, Luh Putu Iin Indrayani; Dewi, I Gusti Ayu Sri Mahendra; Muliarta, I Made; Muliarta, I Made; Sriwidyani, Ni Putu (E-Jurnal Medika Udayana, 2021)
Cervical cancer is the second most common malignancy in women with increasing morbidity and mortality rate. VEGF is known as one of pro-angiogenic factors that induce angiogenesis in various malignancy. VEGF overexpression is associated with poor prognosis and plays an important role in cervical cancer progression. This study aimed to investigate the association between VEGF expression and pathological parameters of squamous cell carcinoma of uterine cervix in Sanglah General Hospital Denpasar. This is a cross-sectional study design. The sampel size was 36 paraffin blocks which were selected by consecutive sampling. Pathological parameter data were divided into 2 categories; tumor size (£4 cm, >4 cm), tumor extension (intra and extra-uterine), lymphatic vascular invasion (positive, negative), vascular density (low, high) and lymph node metastasis (positive, negative). VEGF expressions were examined by imunohistochemical technique and evaluated by Histo-Score method. All variables were analyzed by Chi-square analysis with significance value p <0.05. Chi-square analysis revealed an association between tumor size and VEGF expression (p=0.035). In addition, large tumor size (>4 cm) has 2.17 times probability of causing high VEGF expression. VEGF expression were not associated with tumor extension (p=0.502), lymphatic vascular invasion (p=0.346), vascular density (p=0.364) and lymph node metastasis (p=0.209). This study has proved that tumor size is associated with VEGF expression. Large tumor size has greater risk of causing high VEGF expression therefore anti-VEGF targeted therapy could be proposed in large tumor size. There were no association between VEGF expression and tumor extension, lymphatic vascular invasion, vascular density and lymph node metastasis.   Keywords: VEGF expression, squamous cell carcinoma, uterine cervix.